Contribution to the knowledge of Chinese Phasmatodea II: Review of the Dataminae Rehn & Rehn, 1939 (Phasmatodea: Heteropterygidae) of China, with descriptions of one new genus and four new species - Wai-Chun, George Ho (Zootaxa, 2013)
This paper deals with four genera and eight species of the subfamily Dataminae Rehn & Rehn, 1939 from China. One new genus and four new species, Hainanphasma cristata Ho gen. nov. spec. nov., H. diaoluoshanensis Ho spec. nov., Py-laemenes pui Ho spec. nov. and Pylaemenes shirakii Ho & Brock spec. nov., are described and illustrated. A new combi-nation is proposed: Planispectrum hainanensis (Chen & He, 2008) comb. nov. is transferred from Pylaemenes Stål, 1875 and its male and egg are described for the first time. The occurrence of Orestes mouhotii (Bates, 1865) in China is re-confirmed assessed by an adult specimen collected from Yunnan Province. Pylaemenes guangxiensis (Bi & Li, 1994) is reported for the first time from Vietnam outside the range of China. Keys to the genera and species of the Chinese Datam-inae are given.